Direitos humanos e prática social da comunidade da IECLB, em Cuiabá, MT: dimensão pedagógica da prática do cuidado e de gestão de rede - Witter, Teobaldo (2010)
The present work analyses human rights and its practice the communities of the Evangelical Church of Lutheran the Confession in Brazil (IECLB), in Cuiabá, with the glance for the care and the network administration, in the solidary and pedagogic dimension. The geographical area corresponds to the one of the referred community, enlarged by the inclusion of the homonymous parish of Cuiabá and its suburbs, in the state of Mato Grosso. The chronological scope is delimited by the creation of the parish of Cuiabá and the installation of its first resident pastor, in 1979, and by the event of the 22nd general Assembly of the Evangelical Church of the Lutheran Confession in Brazil, in the year 2000, in Chapada dos Guimarães, in the congregation of Cuiabá, Mato Grosso Synod. The study is divided in three main chapters. It starts from the religious, ecclesial, philosophical, social and of human rights History. In the first chapter, it approaches the theme of human rights, placing it historically and considering the theme. It emphasizes its conceptions as individual, collective and of solidarity rights and the effort of putting them in covenants and declarations, in the juridical orders, its positivations in the Constitution of the Federation and in the first version of the National Program of Human Rights in Brazil. In the second chapter, the analysis refers to the diaconal practice, with emphasis on human rights, in the IECLB and in the New Areas of Colonization (NACs). The study attempts to discuss the insertion of IECLB in the Brazilian social reality. It analyzes the antecedents of the decision to reconcile in 1972, of assisting human persons as a whole and assist all . It also verifies the consequences of such decision to the context of NACs, in the search of a new way of being and living the church. In the third chapter, the study locates essays of the new way of being church, committed with the local reality, faithful to the faith in life and in communion and in witness, in Cuiabá, MT. The study analyzes new ways of being church already practiced, convergences and current divergences in the local church, in the educational process of faith and solidarity, in the ecumenical dimension and in the construction of networks of human rights.